Chrome Hole Dermatitis Due to Work Habit of Electroplating Workers in Candi, Sidoarjo, Indonesia ------ (RETRACTED) - Abdul Hakim Zakkiy Fasya; M. Farid D. Lusno; Setya Haksama (Health Notions, 2018)
This article has been retracted at the request of the authors